Job Satisfaction Among Employees in Private Banks - Mabborang, Jomel; Carsola, Cheyenne; Gatan Jr., Rolie; Monje, Lianne; Ranoco, Patricia (Journal of Interdisciplinary Perspectives, 2025)
This study investigated the factors influencing job satisfaction among employees of private banks in Tuguegarao City, Philippines. Job satisfaction in the workforce is essential for both employees and the business organization. If the employees are satisfied and content, their commitment levels will be high, and hence, their contribution to the organization will also be high. The research explored the demographic profile of respondents (age, gender, civil status, and length of service) and their level of job satisfaction across several factors: performance appraisal, work motivation, salary, co-workers, work environment, and rewards/incentives. A quantitative approach was employed using questionnaires, and data were analyzed using descriptive statistics and inferential tests, such as the Kruskal-Wallis and Mann-Whitney U tests, to determine whether significant differences in job satisfaction existed based on demographic variables. Results indicated that employees generally reported high levels of job satisfaction across all factors, with work motivation being particularly prominent. While age and length of service did not significantly influence job satisfaction, gender revealed a significant difference in perceptions of the work environment, and civil status showed a significant difference in salary satisfaction. The study is grounded in the Theory of Employee Planned Behavior, which emphasizes the crucial role of job satisfaction in driving organizational performance. These findings offer valuable insights for private banks seeking to enhance employee well-being and organizational success.